Central Nervous System Barriers Impact Distribution and Expression of iNOS and Arginase-1 in Infiltrating Macrophages During Neuroinflammation - Ivan, Daniela C.; Walthert, Sabrina; Locatelli, Giuseppe (Frontiers in Immunology, 2021)
In multiple sclerosis (MS) and other neuroinflammatory diseases, monocyte-derived cells (MoCs) traffic through distinct central nervous system (CNS) barriers and gain access to the organ parenchyma exerting detrimental or beneficial functions. How and where these MoCs acquire their different functional commitments during CNS invasion remains however unclear, thus hindering the design of MS treatments specifically blocking detrimental MoC actions. To clarify this issue, we investigated the distribution of iNOS+ pro-inflammatory and arginase-1+ anti-inflammatory MoCs at the distinct border regions of the CNS in a mouse model of MS. Interestingly, MoCs within perivascular parenchymal spaces displayed a predominant pro-inflammatory phenotype compared to MoCs accumulating at the leptomeninges and at the intraventricular choroid plexus (ChP). Furthermore, in an in vitro model, we could observe the general ability of functionally-polarized MoCs to migrate through the ChP epithelial barrier, together indicating the ChP as a potential CNS entry and polarization site for MoCs. Thus, pro- and anti-inflammatory MoCs differentially accumulate at distinct CNS barriers before reaching the parenchyma, but the mechanism for their phenotype acquisition remains undefined. Shedding light on this process, we observed that endothelial (BBB) and epithelial (ChP) CNS barrier cells can directly regulate transcription of Nos2 (coding for iNOS) and Arg1 (coding for arginase-1) in interacting MoCs. More specifically, while TNF-+IFN- stimulated BBB cells induced Nos2 expression in MoCs, IL-1β driven activation of endothelial BBB cells led to a significant upregulation of Arg1 in MoCs. Supporting this latter finding, less pro-inflammatory MoCs could be found nearby IL1R1+ vessels in the mouse spinal cord upon neuroinflammation. Taken together, our data indicate differential distribution of pro- and anti-inflammatory MoCs at CNS borders and highlight how the interaction of MoCs with CNS barriers can significantly affect the functional activation of these CNS-invading MoCs during autoimmune inflammation.